Review and content analysis of mobile apps for inflammatory bowel disease management using the mobile application rating scale (MARS): Systematic search in app stores - Jannati, Nazanin; Salehinejad, Simin; Kuenzig, M. Ellen; Peña-Sánchez, Juan Nicolás (International journal of medical informatics (Shannon, Ireland), 2023)
•Mobile applications designed for individuals with Inflammatory Bowel Disease (IBD) offer various features and tools that help users manage their condition on their own.•The specific functions or features could vary between different IBD mobile applications, but typically, they might include things like tracking symptoms, medication reminders, dietary guidance, access to educational resources, appointment scheduling, and possibly even connecting with support communities or healthcare providers. These functions are intended to empower individuals with IBD to better understand, monitor, and manage their condition, ultimately leading to improved quality of life and health outcomes.•Involving medical professionals and prioritizing user-friendly design can significantly enhance the quality of healthcare-related applications. By incorporating medical expertise, developers can ensure accuracy and clinical relevance, meet regulatory standards, and create apps that truly benefit users. User-friendly design, on the other hand, makes these apps accessible, engaging, and error-resistant, leading to better user experiences and improved health outcomes. People with inflammatory bowel disease (IBD) need tools for self-management of their disease with the ultimate goal of improving medication adherence and health outcomes. Mobile apps represent a novel opportunity to provide self-management for patients with IBD. Many mobile apps have been developed for IBD self-management, but more evidence is needed about the quality of these mobile apps. This study evaluated mobile apps developed for the IBD community and rated the quality of these apps to provide a roadmap for future development. The Apple App Store and Google Play Store were systematically searched to identify IBD mobile apps for patients and physicians based on the IBD-related keywords. We included mobile apps that focus on IBD, are in the English language, and are free. The related app quality was evaluated independently by two reviewers using the Mobile Application Rating Scale (MARS). We identified 401 mobile apps. After removing duplicates and unrelated apps, 44 apps were included in the review. Overall, the mean MARS scores were 3.5 (SD = 0.5) on a scale from 1.00 to 5.00, which was the acceptable range.; 12 apps got scores ≥ 4.00. The highest mean domain score belonged to the functionality dimension (mean = 3.9, SD = 0.6) and the lowest belonged to the engagement dimension (mean = 3.2, SD = 0.8). The MARS ratings showed that the IBD mobile apps quality meet acceptable criteria. However, more attention must be paid to design features that improve user interest and engagement, especially among children and adolescents. Healthcare professional involvement is crucial for designing mobile health apps.